Optomalisasi Kinerja Angkutan Pedesaan Trayek Kalianda-Sidomulyo dan Kalianda-Patok - Veronika Esther Azalia (Jurnal Teknik Sipil, 2025)
Kalianda District is served by rural transportation routes, specifically the Kalianda-Sidomulyo and Kalianda-Patok routes. Currently, public interest in using public transportation is still low. Based on data from the South Lampung Regency Department of Transportation, the load factor for rural transportation has a low percentage. According to the data, the lowest load factor is on the Kalianda-Sidomulyo route at 46% and the Kalianda-Patok route at 33%. These load factor percentages have not yet reached the established standard of 70% (the minimum load factor standard according to the Director General of Land Transportation’s Decree No. 687 of 2002 on Technical Guidelines for Urban Public Passenger Transportation on Fixed and Regular Routes), resulting in minimal revenue for operators.The aim of this study is to determine the number of vehicles needed for all rural transport routes in South Lampung Regency, to analyze the revenue earned by operators on the Kalianda-Sidomulyo and Kalianda-Patok routes, and to calculate the Vehicle Operational Costs (BOK) for these routes. The methods used in this study include fleet requirement analysis using the Load Factor Break-Even Point and operator profit/loss analysis. Recommendations are provided in the form of reducing the number of vehicles to prevent losses for both operators and passengers.